Optimization and validation of analytical RP-HPLC methods for the quantification of glucosinolates and isothiocyanates in Nasturtium officinale R. Br and Brassica oleracea. (1st August 2022) - Theunis, Mart; Naessens, Tania; Peeters, Laura; Brits, Maxime; Foubert, Kenn; Pieters, Luc
Abstract: Watercress contains a considerable amount of vitamins, minerals and secondary metabolites and is used in food and for its medicinal properties. These latter are mainly attributed to glucosinolates which are precursors of bioactive compounds such as isothiocyanates. Broccoli is an edible vegetable of the family Brassicaceae that is rich in vitamins and secondary metabolites. Because of the biological activity of sulforaphane, broccoli became a popular food supplement. However, broccoli also contains the glucosinolate progoitrin and its derivative goitrin, an antithyroid compound and goitrogen, which can enlarge the thyroid gland. To avoid these effects, the daily intake of progoitrin and goitrin are limited to 20 mg and 5 mg. Since the quality of the food supplements of watercress and broccoli depends on the content of glucosinolates and their derivatives, quantitative HPLC methods were developed and validated conform the ICH guidelines to analyse the glucosinolates, phenylethyl isothiocyanate and goitrin. The methods were linear in the ranges 0.084–0.418 μmol/mL(gluconasturtiin), 0.013–1.04 μmol/mL (phenylethyl isothiocyanate), 0.044–1.312 μmol/mL (glucotropaeolin) and 0.0077–3.0965 μmol/mL (goitrin). The precision of the methods with respect to time and concentration was acceptable. A recovery of 99.2% and 100.6% was obtained for progoitrin and goitrin. Graphical abstract: Image 1 Highlights: Optimization/validation of the analytical method for glucosinolates in watercress. Optimization/validation of the analytical method for isothiocyanates in watercress. Optimization/validation of the analytical method for progoitrin and goitrin. Analysis of progoitrin and goitrin in commercial products.